Direct‐Write Freeform Colloidal Assembly. Issue 44 (30th August 2018) - Tan, Alvin T. L.; Beroz, Justin; Kolle, Mathias; Hart, A. John
Abstract: Colloidal assembly is an attractive means to control material properties via hierarchy of particle composition, size, ordering, and macroscopic form. However, despite well‐established methods for assembling colloidal crystals as films and patterns on substrates, and within microscale confinements such as droplets or microwells, it has not been possible to build freeform colloidal crystal structures. Direct‐write colloidal assembly, a process combining the bottom‐up principle of colloidal self‐assembly with the versatility of direct‐write 3D printing, is introduced in the present study. By this method, centimeter‐scale, free‐standing colloidal structures are built from a variety of materials. A scaling law that governs the rate of assembly is derived; macroscale structural color is tailored via the size and crystalline ordering of polystyrene particles, and several freestanding structures are built from silica and gold particles. Owing to the diversity of colloidal building blocks and the means to control their interactions, direct‐write colloidal assembly could therefore enable novel composites, photonics, electronics, and other materials and devices. Abstract : Direct‐write colloidal assembly enables the fabrication of freestanding structures with centimeter‐scale dimensions. The 3D colloidal structures are polycrystalline and display structural color, which is tunable by particle size. By controlling the macroscale form via the direct‐write tool‐path, and controlling the particle arrangement via self‐assembly, this technique could broadly enable additive manufacturing of ordered colloidal solids for photonics, electronics, and other applications.